Hypertension and Recurrent Hypokalaemia in Young Woman - A Case Report of Primary Hyperaldosteronism (Conn’s Syndrome) - Hasan, Md Nazmul; Rahim, Md Abdur; Ahmed, Quazi Mamtaz Uddin; Islam, Md Syedul; Amin, Md Rasul; Rahman, Md Atikur; Amin, Md Nurul (University Heart Journal, 2018)
Primary hyperaldosteronism is caused by most commonly due to aldosterone producing adenoma(conn’s syndrome) or bilateral adrenal hyperplasia. Clinical features may be of different type which includes hypertension in young age or resistant hypertension, recurrent hypokalaemia and characterized by increased ratio of plasma aldosterone (ng/dl) to rennin (ng/ml per hour) activity. We report a case of young woman presented with hypertension and recurrent hypokalaemia. University Heart Journal Vol. 12, No. 2, July 2016; 102-104